Swine Flu Progressive Pulmonary Fibrosis – Clinical Manifestation and Morphology of Explanted Lungs - Shirish Sahebrao Chandanwale; Madhuri Singh; Akshi Raj; Charusheela Gore; Namit Gupta (Indian Journal of Transplantation)
Novel influenza A (H1N1) virus also known as swine flu results from the combination of genetic elements from swine, human, and avian viruses. During the 2009 swine flu pandemic, millions of people got infected with swine flu. Between April 2009 and April 2010, a large number of deaths were reported. The virus is antigenetically distinct from seasonal influenza infection and is usually sensitive to oseltamivir. In recent years, sporadic cases of swine flu have been reported globally. There has been spurt in swine flu cases in India in recent years. Although a large number of swine flu patients present with acute respiratory distress syndrome, majority of these patients show complete recovery without leaving any residual illness. Few cases show residual fibrosis on high-resolution computed tomography after recovery. Even with high degree suspicion, clinical diagnosis is difficult. Confirmatory laboratory tests are essential for definitive diagnosis. We report a case of a 54-year-old female without any comorbidities who developed progressive pulmonary fibrosis and she required bilateral lung transplant.